Cellulose/SnS2 composite with enhanced visible-light photocatalytic activity prepared by microwave-assisted ionic liquid method. Issue 20 (21st February 2017) - Lin, Chunxiang; Zhu, Moshuqi; Zhang, Teng; Liu, Yifan; Lv, Yuancai; Li, Xiaojuan; Liu, Minghua
Abstract : IL type influences the morphology of SnS2 prepared by MAIL methods. Cellulose support enhances the performance of as-synthesized CE/SnS2 composite. Abstract : A facile method was used to synthesize cellulose/SnS2 composites (CE/SnS2 ) by a microwave-assisted ionic liquid (MAIL) method. The effects of ionic liquid types on the structure and properties of SnS2 samples were investigated. Results showed that the ionic liquid played an important role in the control over the morphology, size and photocatalytic performance of the SnS2 particles. The as-synthesized CE/SnS2 composites were systematically investigated by XRD, SEM, TEM, BET, XPS, UV-visible and PL. It was demonstrated that the obtained CE/SnS2 composites showed three-dimensional architecture and excellent visible-light photocatalytic activity as photocatalyst for RhB degradation. The superior visible-light photocatalytic performances for composites were ascribed to their composite structure and the synergistic effects between flower-like SnS2 and cellulose.